Countrywide survey on ISO 9001-certified companies in Malaysian construction industry - Sia, Mal Kong; Gomez, Christy Pathrose (Construction Research Institute of Malaysia, 2009)
This article reports part of the results collected from 100 ISO 9001-certified companies in the Malaysian construction industry for a PhD research. Construction industry has bad public image because of safety, delay and quality issues. This is due to extreme segmentation and fragmentation of the supply chain, which cause difficulties in managing quality in construction industry. Due to low quality and low productivity, there is a need to implement ISO 9001 quality management system. This article helps to address the lack of data and information identified by CIDB Malaysia by documenting the extent to which Malaysian construction companies are accredited with ISO 9001 certifications, summarising the motivations behind the pursuit for ISO 9001 certifications, investigating the reasons for firms to obtain and maintain ISO 9001 certifications status in their organisations, and reviewing the extent to which ISO 9001-certified companies have gained benefits through the implementation of ISO 9001 quality management system. The results reveal that companies in the Malaysian construction industry adopt ISO 9001 certifications mainly to enhance their competitive processes and competitive performance to enable them to operate more efficiently.